+0  
 
+1
61
1
avatar+821 

Multiply

AngelRay  Mar 4, 2018
Sort: 

1+0 Answers

 #1
avatar+12266 
+1

=  sqrt ( (24*18*15)*(x*y*y)  )

= sqrt ( ( 2^2 *6  *  3^2 *2  * 15 )  *  xy^2  )

= 2*3*y  sqrt(6 *2*15 x)

= 6y  sqrt( 180 x)

= 6y sqrt ( 36 * 5  x)

= 6y sqrt (6^2 * 5x)

= 36 y sqrt (5x)  

ElectricPavlov  Mar 4, 2018

14 Online Users

New Privacy Policy (May 2018)
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  Privacy Policy